(untitled) (World Economics and Finance Bulletin, 2024)
This research aims to identify the role of integrated reports in bridging the gap between the request and supply of accounting information to meet the information needs of investors to guide them in making their investment decisions and reduce risks. The two researchers reached a set of results, the most important of which is that there are no statistically significant differences between the categories of respondents regarding the characteristics of... Integrated reports: There is agreement among the respondents about these features. The research also found that there is a significant impact between integrated reports in reducing the gap in the supply and demand of accounting information to meet the needs of investors. The research recommends the necessity of adopting integrated business reports to further improve the level of disclosure, which is reflected in decisions. Investors.